Bisexuality, Slippery Slopes, and Multipartner Marriage. Issue 1 (2nd January 2018) - Klesse, Christian
ABSTRACT: This article explores the position of polyamory in slippery slope arguments directed against the campaign for same-sex marriage rights in the United States. In the rhetoric of right-wing opponents granting same-sex marriage rights is seen as the first step on a long spiral downwards toward moral decay, which will successively normalize a whole range of problematic and 'unwanted' practices. Polygamy and, in its close proximity, polyamory are usually the first items on a list that may also include adultery, adult incest, bestiality, and pedophilia. The article highlights the mobilization of racist and nationalist tropes at the heart of antipolygamy sentiments and considers the impact of this legacy for poly politics. Concentrating on the analysis of essays published by the Conservative journalist Stanley Kurtz, the article explores the connection between bisexuality and polyamory in some slippery slope arguments. slippery slope arguments have been a constant feature of the debates about same-sex marriage rights in the United States. Their relative prominence and strong hold within the public imagination have also affected the discourses deployed by poly activists, resulting in common disassociations from polygamy and an a reluctance to engage with questions regarding the legal recognition of multipartner relationships at all. Understanding the slippery slope dynamic is important for grasping the conditionality that contributes to the persisting hostilities against polyamory, polygamy, and LGBTQ intimacies and that shapes social movement politics.